Activated carbon for water treatment and production method thereof
Through the combined use of modified activated carbon and composite xanthan gum, the problem of insufficient adsorption performance of ordinary activated carbon is solved, and the adsorption capacity and water treatment efficiency of activated carbon for water treatment are significantly improved.
Patent Information
- Application Number
- CN202411697842.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the preparation process, ordinary activated carbon for water treatment is affected by raw materials and process conditions, and the pore structure and surface chemistry are limited, resulting in limited adsorption effect and it is difficult to meet the complex and changeable water pollution problems.
Modified activated carbon and composite xanthan gum participate in the preparation of activated carbon for water treatment. By esterification of oxidized activated carbon and end amino silicone oil, nitrogen and silicon elements are increased, and the cohesion of xanthan gum is enhanced through alkenylation and radical polymerization. Bonding strength.
The specific surface area and adsorption capacity of activated carbon for water treatment are improved, the hydrophobic capacity is enhanced, the adsorption efficiency of heavy metal ions and organic pollutants is improved, and the water treatment efficiency is significantly improved.
Smart Images

Figure CN119455896A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of activated carbon, and in particular to activated carbon for water treatment and a production method thereof. Background Art
[0002] With the rapid development of industrialization and urbanization, a large amount of untreated sewage is directly discharged into the environment. The problem of water pollution is becoming increasingly serious, posing a huge threat to human health and ecological balance. Therefore, water treatment technology has become an important measure to protect water resource security.
[0003] Pollutants in sewage can be roughly divided into two types: inorganic pollutants and organic pollutants. Among the many water treatment materials, activated carbon has unique adsorption properties and has a good removal effect on both organic and inorganic pollutants. It can effectively improve water quality and increase the utilization rate of water resources. However, ordinary activated carbon is affected by factors such as raw materials and process conditions during the preparation process, and its pore structure and surface chemical properties often have certain limitations. This leads to limited adsorption when dealing with complex and changeable water pollution problems, and it is difficult to meet the use requirements of activated carbon for water treatment in various environments.
[0004] Therefore, how to improve the adsorption capacity of activated carbon has become a hot research topic. For example, the patent with publication number CN107175073B discloses a preparation method and application of activated carbon for water treatment. The activated carbon is modified by potassium ferrate and copper sulfate, and loaded with titanium dioxide and a chelating agent, so that the prepared activated carbon has a large specific surface area and good adsorption capacity, and has a wide range of applications. For example, the patent with publication number CN103495389B discloses a modified straw activated carbon water treatment agent and a preparation method thereof. The activated carbon water treatment agent uses sodium montmorillonite with good cation exchange function, which can remove heavy metal ions in water. Flocculants such as aluminum sulfate and sodium carbonate are also added to further remove pollutants such as bacteria in water, and have a good purification effect on water. Summary of the invention
[0005] The purpose of the present invention is to provide an activated carbon for water treatment and a production method thereof, which solves the problem that ordinary activated carbon for water treatment has general adsorption performance and weak water treatment effect.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] An activated carbon for water treatment, comprising the following raw materials in parts by weight: 50-80 parts of modified activated carbon, 6-8 parts of fly ash, 5-6 parts of diatomaceous earth, 3-5 parts of zeolite powder, and 8-10 parts of composite xanthan gum;
[0008] The modified activated carbon is prepared from oxidized activated carbon and amino-terminated silicone oil; the oxidized activated carbon is prepared from coconut shell activated carbon oxidized by nitric acid;
[0009] The composite xanthan gum is prepared by free radical polymerization of olefinic xanthan gum and diallylamine; the olefinic xanthan gum is prepared by xanthan gum and glycidyl methacrylate.
[0010] Furthermore, the preparation method of the modified activated carbon comprises the following steps:
[0011] S1: Place coconut shell activated carbon in a nitric acid solution, heat to 60-65°C for 4-6 hours, wash with deionized water, filter, and dry to obtain oxidized activated carbon;
[0012] S2: Place the oxidized activated carbon in deionized water, ultrasonically disperse it for 10-15 minutes, introduce nitrogen, add amino-terminated silicone oil and composite catalyst, heat to 55-60°C and stir for 5-8 hours, filter, wash and dry to obtain modified activated carbon.
[0013] In this scheme, coconut shell activated carbon is oxidized with nitric acid solution to obtain oxidized activated carbon with carboxyl groups, and then under the action of a composite catalyst, the carboxyl groups in the oxidized activated carbon undergo esterification reaction with the amino groups in the terminal amino silicone oil structure to obtain modified activated carbon. The modified activated carbon contains nitrogen and silicon elements, and their participation in the preparation process of activated carbon for water treatment can not only increase the specific surface area of the activated carbon for water treatment, so that it can expose more active adsorption sites and improve the adsorption capacity, but also enhance its hydrophobic ability, weaken the adsorption force of activated carbon for water treatment on water molecules, and enhance the contact probability with target pollutants, thereby further improving the adsorption effect of activated carbon for water treatment.
[0014] Furthermore, in step S1, the mass fraction of the nitric acid solution is 30-35%.
[0015] Furthermore, in step S2, the composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 0.16-2:0.05-0.7.
[0016] Furthermore, the preparation method of the composite xanthan gum comprises the following steps:
[0017] SS1: Place glycidyl methacrylate in tetrahydrofuran, add xanthan gum, swell at room temperature for 2-3 hours, add catalyst, heat to 50-55°C and react for 6-8 hours, remove the solvent by vacuum distillation and collect the product to obtain olefinated xanthan gum;
[0018] SS2: Place olefinated xanthan gum in deionized water, stir and mix thoroughly, add diallylamine and azobisisobutyronitrile, heat and stir, remove the solvent by rotary evaporation and collect the product to obtain composite xanthan gum.
[0019] In this scheme, under the action of a catalyst, the hydroxyl groups in the xanthan gum structure and the epoxy groups in the glycidyl methacrylate structure undergo a ring-opening reaction to obtain olefinic xanthan gum, and then under the action of azobisisobutyronitrile, multiple double bonds in the olefinic xanthan gum structure and two double bonds in the diallylamine structure undergo free radical polymerization to obtain composite xanthan gum. This composite xanthan gum has excellent cohesive force, and at the same time, its structure has a large number of ether bonds, which can effectively enhance the bonding strength. It exhibits excellent bonding properties when preparing activated carbon for water treatment. Only a small amount is needed to tightly connect the components, effectively reducing the possibility of reduced adsorption effect of activated carbon for water treatment due to excessive binder.
[0020] Furthermore, in step SS1, the catalyst is tetrabutylammonium bromide or triethylamine.
[0021] Furthermore, in step SS2, the temperature of the heating and stirring is 55-65° C., and the time is 3-6 hours.
[0022] A method for producing activated carbon for water treatment comprises the following steps:
[0023] Step 1: Place modified activated carbon, fly ash, diatomaceous earth, zeolite powder and composite xanthan gum in a high-speed mixer and stir for 1-2 hours to form a mixture;
[0024] Step 2: Place the mixture in a mold and press it into shape. After drying at 100-120°C for 6-8 hours, place it in a sintering furnace, introduce argon gas, increase the temperature to 480-500°C, roast for 3-5 hours, cool naturally, cut and bag, and seal to obtain activated carbon for water treatment.
[0025] Furthermore, in step 1, the rotation speed of the high-speed mixer is 800-1200 r / min.
[0026] Furthermore, in step 2, the heating rate of the increased temperature is 20-22°C / min.
[0027] Beneficial effects of the present invention:
[0028] The present invention prepares modified activated carbon and composite xanthan gum to participate in the preparation process of activated carbon for water treatment, so that the prepared activated carbon for water treatment has excellent adsorption capacity, can effectively adsorb heavy metal ions and organic pollutants in wastewater, has large adsorption capacity, and has excellent wastewater treatment efficiency.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 This is a flow chart for preparing activated carbon for water treatment according to the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The preparation methods of modified activated carbon and composite xanthan gum in the following examples and comparative examples of the present invention are as follows:
[0034] 1. Preparation of modified activated carbon
[0035] S1: 3 g coconut shell activated carbon was placed in 25 ml 30% nitric acid solution, heated to 60 ° C for 4 h, washed with deionized water, filtered, and dried to obtain oxidized activated carbon;
[0036] The acid-base titration method is used to test the carboxyl content in the oxidized activated carbon. The specific operation is as follows: 1g of the oxidized activated carbon is placed as a sample in 60ml of butanone solution, an excess of a potassium hydroxide ethanol standard solution with a concentration of 0.1mol / L is added, 2 drops of phenolphthalein indicator are added, and after sufficient mixing, a hydrochloric acid standard solution with a concentration of 0.1mol / L is used for back titration until the color changes significantly. At the same time, a blank experiment is performed, and the volumes of the potassium hydroxide ethanol standard solution and the hydrochloric acid standard solution consumed are recorded, and the calculation is performed according to the following formula: carboxyl mass fraction (%) = 0.045×c(V-V0)×100% / m; wherein c is the concentration of the hydrochloric acid standard solution, mol / L; V is the volume of the hydrochloric acid standard solution consumed, ml; V0 is the volume of the hydrochloric acid standard solution consumed in the blank sample, ml; m is the sample mass, g; 0.045 is the molar mass of the carboxyl group, kg / mol; after calculation, the carboxyl content in the oxidized activated carbon is 5.7%.
[0037] S2: Place 3.8 g of oxidized activated carbon in 60 ml of deionized water, ultrasonically disperse for 10 min, introduce nitrogen, add 3 g of terminal amino silicone oil, 0.16 g of dicyclohexylcarbodiimide and 0.05 g of 4-dimethylaminopyridine, heat to 55 ° C and stir for 5 h, filter, wash and dry to obtain modified activated carbon.
[0038] The carboxyl content in the modified activated carbon was tested by acid-base titration method. The specific operation steps were the same as S1. After calculation, the carboxyl content in the modified activated carbon was 0.9%. The decrease in the carboxyl content was due to the esterification reaction between the carboxyl groups in the oxidized activated carbon and the amino groups in the terminal amino silicone oil structure.
[0039] Coconut shell activated carbon is treated with nitric acid as a strong oxidant, carboxyl groups are introduced into the coconut shell activated carbon, and then under the composite catalysis of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the carboxyl groups in the coconut shell activated carbon and the amino groups in the terminal amino silicone oil structure undergo esterification reaction to obtain modified activated carbon. This modified activated carbon contains nitrogen and silicon elements, which can not only enhance the adsorption performance of the activated carbon, but also when used for water treatment, the presence of silicon elements can enhance the hydrophobicity of the activated carbon, thereby enhancing the contact probability between the activated carbon and the target pollutants, thereby enhancing the activated carbon's adsorption capacity for pollutants.
[0040] The water contact angles of oxidized activated carbon and modified activated carbon were tested using a JC2000D2G contact angle tester. The test showed that the surface contact angle of oxidized activated carbon was 101.3°; the surface contact angle of modified activated carbon was 122.1°. The modified activated carbon had better hydrophobic properties.
[0041] The coconut shell activated carbon, oxidized activated carbon and modified activated carbon were tested using a BSD-PM specific surface area and micropore analyzer. The specific test results are shown in the table below:
[0042] <![CDATA[Specific surface area / m 2 / g]]> <![CDATA[Pore volume / cm 3 / g]]> Pore diameter / nm Modified activated carbon 2334 2.643 3.024 Oxidized activated carbon 1528 0.146 4.648 Coconut Shell Activated Carbon 812 0.104 5.932
[0043] It can be seen from the above table that the modified activated carbon has a higher specific surface area, a larger pore volume and a smallest pore size, more adsorption sites and excellent adsorption performance.
[0044] 2. Preparation of composite xanthan gum
[0045] SS1: 2.5 g of glycidyl methacrylate was placed in 50 ml of tetrahydrofuran, 3.2 g of xanthan gum was added, and the mixture was swollen at room temperature for 2 h. 0.03 g of tetrabutylammonium bromide was added, and the mixture was heated to 50°C and reacted for 6 h. The solvent was removed by distillation under reduced pressure and the product was collected to obtain olefinated xanthan gum.
[0046] SS2: Place 2.8 g of olefinated xanthan gum in 80 ml of deionized water, stir thoroughly to mix, add 3 g of diallylamine and 0.2 g of azobisisobutyronitrile, heat to 55°C and stir for 3 h, remove the solvent by rotary evaporation and collect the product to obtain composite xanthan gum.
[0047] The CHN-8000B fully automatic elemental analyzer was used to perform nitrogen element analysis on olefinated xanthan gum and composite xanthan gum. The results showed that olefinated xanthan gum did not contain nitrogen, while the nitrogen content of composite xanthan gum was 3.8%. This was due to the free radical polymerization reaction between the olefinic groups in the olefinated xanthan gum structure and the olefinic groups in the diallylamine structure, which introduced amine groups into the composite xanthan gum structure.
[0048] Under the catalytic action of tetrabutylammonium bromide, the epoxy group in the structure of glycidyl methacrylate and the hydroxyl group in the structure of xanthan gum undergo a ring-opening reaction to obtain olefinic xanthan gum. Then, under the initiation of azobisisobutyronitrile, the double bonds in the structure of diallylamine and the double bonds in the structure of olefinic xanthan gum undergo free radical polymerization to form a network structure to enhance the cohesion and bonding strength of the xanthan gum.
[0049] With reference to the standard GB / T14074-2017, pine wood boards with a thickness of 15 mm were used as the base material to test the bonding strength of xanthan gum, olefinic xanthan gum and composite xanthan gum. The test showed that the bonding strength of xanthan gum was 0.301 MPa; the bonding strength of olefinic xanthan gum was 0.521 MPa; and the bonding strength of composite xanthan gum was 0.679 MPa. It can be seen that composite xanthan gum has excellent bonding strength because its structure contains a large number of ether bonds, which can enhance the adhesion with the matrix, and it also has excellent cohesion, which significantly enhances the bonding strength of composite xanthan gum.
[0050] Example 1
[0051] Preparation of activated carbon for water treatment
[0052] Step 1: Place 50g of modified activated carbon, 6g of fly ash, 5g of diatomaceous earth, 3g of zeolite powder, and 8g of composite xanthan gum in a high-speed mixer, and stir at a speed of 800r / min for 1h to form a mixture;
[0053] Step 2: Place the mixture in a mold and press it into shape. After drying at 100°C for 6 hours, place it in a sintering furnace, introduce argon gas, and heat it to 480°C at a rate of 20°C / min. After roasting for 3 hours, cool it naturally, cut it, bag it, and seal it to obtain activated carbon for water treatment.
[0054] Example 2
[0055] Preparation of activated carbon for water treatment
[0056] Step 1: Place 65g of modified activated carbon, 7g of fly ash, 5.5g of diatomaceous earth, 4g of zeolite powder, and 9g of composite xanthan gum in a high-speed mixer, and stir at a speed of 1000r / min for 1.5h to form a mixture;
[0057] Step 2: Place the mixture in a mold and press it into shape. After drying at 110°C for 7 hours, place it in a sintering furnace, introduce argon gas, and heat it to 490°C at a rate of 21°C / min. After roasting for 4 hours, cool it naturally, cut it, and seal it in bags to obtain activated carbon for water treatment.
[0058] Example 3
[0059] Preparation of activated carbon for water treatment
[0060] Step 1: Place 80g of modified activated carbon, 8g of fly ash, 6g of diatomaceous earth, 5g of zeolite powder, and 10g of composite xanthan gum in a high-speed mixer, and stir at a speed of 1200r / min for 2h to form a mixture;
[0061] Step 2: Place the mixture in a mold and press it into shape. After drying at 120°C for 8 hours, place it in a sintering furnace, introduce argon gas, and heat it to 500°C at a rate of 22°C / min. After roasting for 5 hours, cool it naturally, cut it, bag it, and seal it to obtain activated carbon for water treatment.
[0062] Comparative Example 1
[0063] Preparation of activated carbon for water treatment
[0064] Step 1: Place 65g coconut shell activated carbon, 7g fly ash, 5.5g diatomaceous earth, 4g zeolite powder, and 9g composite xanthan gum in a high-speed mixer, and stir at a speed of 1000r / min for 1.5h to form a mixture;
[0065] Step 2: Place the mixture in a mold and press it into shape. After drying at 110°C for 7 hours, place it in a sintering furnace, introduce argon gas, and heat it to 490°C at a rate of 21°C / min. After roasting for 4 hours, cool it naturally, cut it, and seal it in bags to obtain activated carbon for water treatment.
[0066] Comparative Example 2
[0067] Preparation of activated carbon for water treatment
[0068] Step 1: Place 65g of modified activated carbon, 7g of fly ash, 5.5g of diatomaceous earth, 4g of zeolite powder, and 9g of xanthan gum in a high-speed mixer, and stir at a speed of 1000r / min for 1.5h to form a mixture;
[0069] Step 2: Place the mixture in a mold and press it into shape. After drying at 110°C for 7 hours, place it in a sintering furnace, introduce argon gas, and heat it to 490°C at a rate of 21°C / min. After roasting for 4 hours, cool it naturally, cut it, and seal it in bags to obtain activated carbon for water treatment.
[0070] Comparative Example 3
[0071] Preparation of activated carbon for water treatment
[0072] Step 1: Place 65g coconut shell activated carbon, 7g fly ash, 5.5g diatomaceous earth, 4g zeolite powder, and 9g xanthan gum in a high-speed mixer, and stir at a speed of 1000r / min for 1.5h to form a mixture;
[0073] Step 2: Place the mixture in a mold and press it into shape. After drying at 110°C for 7 hours, place it in a sintering furnace, introduce argon gas, and heat it to 490°C at a rate of 21°C / min. After roasting for 4 hours, cool it naturally, cut it, and seal it in bags to obtain activated carbon for water treatment.
[0074] Comparative Example 4
[0075] Preparation of activated carbon for water treatment
[0076] Step 1: Place 65g of oxidized activated carbon, 7g of fly ash, 5.5g of diatomaceous earth, 4g of zeolite powder, and 9g of composite xanthan gum in a high-speed mixer, and stir at a speed of 1000r / min for 1.5h to form a mixture;
[0077] Step 2: Place the mixture in a mold and press it into shape. After drying at 110°C for 7 hours, place it in a sintering furnace, introduce argon gas, and heat it to 490°C at a rate of 21°C / min. After roasting for 4 hours, cool it naturally, cut it, and seal it in bags to obtain activated carbon for water treatment.
[0078] Comparative Example 5
[0079] Preparation of activated carbon for water treatment
[0080] Step 1: Place 65g of modified activated carbon, 7g of fly ash, 5.5g of diatomaceous earth, 4g of zeolite powder, and 9g of olefinized xanthan gum in a high-speed mixer, and stir at a speed of 1000r / min for 1.5h to form a mixture;
[0081] Step 2: Place the mixture in a mold and press it into shape. After drying at 110°C for 7 hours, place it in a sintering furnace, introduce argon gas, and heat it to 490°C at a rate of 21°C / min. After roasting for 4 hours, cool it naturally, cut it, and seal it in bags to obtain activated carbon for water treatment.
[0082] Performance Testing
[0083] The COD of activated carbon for water treatment prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to the test method specified in the "Water and Wastewater Monitoring and Analysis Methods" (Fourth Edition); the copper ion content in the wastewater sample and the effluent sample was tested by atomic absorption spectroscopy. The copper ion content in the wastewater was 515 mg / L. The heavy metal ion removal rate was calculated according to the following formula: Heavy metal ion removal rate = (F-F1) × 100% / F; wherein F is the heavy metal ion content in the wastewater sample, mg / L; F1 is the heavy metal ion content in the effluent sample, mg / L; the specific test results are shown in the following table:
[0084] Heavy metal ion removal rate / % COD removal rate / % Example 1 88.6 86.9 Example 2 89.6 87.3 Example 3 89.2 87.0 Comparative Example 1 77.4 75.8 Comparative Example 2 76.8 73.5 Comparative Example 3 61.7 62.4 Comparative Example 4 79.9 78.6 Comparative Example 5 82.3 81.7
[0085] It can be seen from the above table that the activated carbon for water treatment prepared in Examples 1 to 3 has excellent heavy metal adsorption capacity and COD adsorption capacity. The activated carbon for water treatment prepared in Comparative Example 1 has not been modified, and its adsorption capacity is not as good as that of the embodiment. The activated carbon for water treatment prepared in Comparative Example 2 uses modified activated carbon, and uses xanthan gum as a binder, but does not enhance its bonding strength. The insufficient bonding strength affects the bonding between the components of the activated carbon for water treatment and reduces its adsorption capacity. The activated carbon for water treatment prepared in Comparative Example 3 directly uses coconut shell activated carbon and xanthan gum, and has poor adsorption performance. The activated carbon for water treatment prepared in Comparative Example 4 uses oxidized activated carbon. Although the adsorption performance is enhanced, it is not as good as that of the embodiment. The activated carbon for water treatment prepared in Comparative Example 5 uses olefinic xanthan gum as an adhesive, has good bonding strength and good adsorption performance, but is not as good as that of the embodiment.
[0086] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0087] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. An activated carbon for water treatment, characterized in that: The method comprises the following raw materials in parts by weight: 50-80 parts of modified activated carbon, 6-8 parts of fly ash, 5-6 parts of diatomaceous earth, 3-5 parts of zeolite powder, and 8-10 parts of composite xanthan gum; The modified activated carbon is prepared from oxidized activated carbon and amino-terminated silicone oil; the oxidized activated carbon is prepared from coconut shell activated carbon oxidized by nitric acid; The composite xanthan gum is prepared by free radical polymerization of olefinated xanthan gum and diallylamine; the olefinated xanthan gum is prepared by xanthan gum and glycidyl methacrylate.
2. The activated carbon for water treatment according to claim 1, characterized in that: The preparation method of the modified activated carbon comprises the following steps: S1: Place coconut shell activated carbon in a nitric acid solution, heat to 60-65°C for 4-6 hours, wash with deionized water, filter, and dry to obtain oxidized activated carbon; S2: Place the oxidized activated carbon in deionized water, ultrasonically disperse it for 10-15 minutes, introduce nitrogen, add amino-terminated silicone oil and composite catalyst, heat to 55-60°C and stir for 5-8 hours, filter, wash and dry to obtain modified activated carbon.
3. The activated carbon for water treatment according to claim 2, characterized in that: In step S1, the mass fraction of the nitric acid solution is 30-35%.
4. The activated carbon for water treatment according to claim 2, characterized in that: In step S2, the composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 0.16-2:0.05-0.
7.
5. The activated carbon for water treatment according to claim 1, characterized in that: The preparation method of the composite xanthan gum comprises the following steps: SS1: Place glycidyl methacrylate in tetrahydrofuran, add xanthan gum, swell at room temperature for 2-3 hours, add catalyst, heat to 50-55°C and react for 6-8 hours, remove the solvent by vacuum distillation and collect the product to obtain olefinated xanthan gum; SS2: Place olefinated xanthan gum in deionized water, stir and mix thoroughly, add diallylamine and azobisisobutyronitrile, heat and stir, remove the solvent by rotary evaporation and collect the product to obtain composite xanthan gum.
6. The activated carbon for water treatment according to claim 5, characterized in that: In step SS1, the catalyst is tetrabutylammonium bromide or triethylamine.
7. The activated carbon for water treatment according to claim 5, characterized in that: In step SS2, the temperature of the heating and stirring is 55-65° C., and the time is 3-6 hours.
8. A method for producing activated carbon for water treatment according to claim 1, characterized in that: The following steps are involved: Step 1: Place modified activated carbon, fly ash, diatomaceous earth, zeolite powder and composite xanthan gum in a high-speed mixer and stir for 1-2 hours to form a mixture; Step 2: Place the mixture in a mold and press it into shape. After drying at 100-120°C for 6-8 hours, place it in a sintering furnace, introduce argon gas, increase the temperature to 480-500°C, roast for 3-5 hours, cool naturally, cut and bag, and seal to obtain activated carbon for water treatment.
9. The method for producing activated carbon for water treatment according to claim 8, characterized in that: In step 1, the rotation speed of the high-speed mixer is 800-1200 r / min.
10. The method for producing activated carbon for water treatment according to claim 8, characterized in that: In step 2, the heating rate of the temperature increase is 20-22°C / min.
Citation Information
Patent Citations
A modified straw activated carbon water treatment agent and preparation method thereof
CN103495389B
A method for preparing activated carbon for water treatment and its application
CN107175073B